2022
DOI: 10.1021/jacs.2c07370
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Polysubstituted Spiropentanes

Abstract: A new approach to polysubstituted spiropentanes is developed through a regio-and diastereoselective carbometalation of sp 2 -disubstituted cyclopropenes. The control of selectivity originates from a combined syn-facial diastereoselective carbometalation with a regio-directed addition. The regio-controlling element subsequently serves as a leaving group in an intramolecular nucleophilic substitution. This method allows the preparation of various polysubstituted spiropentanes with up to five contiguous stereocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Our group has recently reported an efficient and straightforward synthesis of stereodefined polysubstitued spiropentanes 3. 65 The method involves a diastereoselective carbocupration reaction of cyclopropenes cyclopropyl copper species 2, which subsequently cyclize to produce the expected spiropentanes 3 (Scheme 2a) with excellent diastereoselectivity. Motivated by the success of this approach, we set out to utilize the cyclization of cyclopropyl metal species to stereoselectively produce BCBs (Scheme 2b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently reported an efficient and straightforward synthesis of stereodefined polysubstitued spiropentanes 3. 65 The method involves a diastereoselective carbocupration reaction of cyclopropenes cyclopropyl copper species 2, which subsequently cyclize to produce the expected spiropentanes 3 (Scheme 2a) with excellent diastereoselectivity. Motivated by the success of this approach, we set out to utilize the cyclization of cyclopropyl metal species to stereoselectively produce BCBs (Scheme 2b).…”
mentioning
confidence: 99%
“…Our group has recently reported an efficient and straightforward synthesis of stereodefined polysubstitued spiropentanes 3 . The method involves a diastereoselective carbocupration reaction of cyclopropenes 1 to generate cyclopropyl copper species 2 , which subsequently cyclize to produce the expected spiropentanes 3 (Scheme a) with excellent diastereoselectivity.…”
mentioning
confidence: 99%
“…Considering the efficiency and atom economy, ring-retentive functionalization of cyclopropene is the most attractive alternative for forming polysubstituted cyclopropanes . The Marek and Fox groups have made tremendous efforts in this field after Nakamura’s pioneering work for Fe-catalyzed carbometalation of cyclopropene . Different methods have been published on transition metal (Pd, Rh, Cu, Co, etc.)…”
mentioning
confidence: 99%
“…During our studies on the diastereoselective synthesis of polysubstituted cyclopropanes as a new source of stereodefined acyclic products, we have recently shown that alkenyl cyclopropyl carbinol derivatives 1 exhibit an excellent directing effect for the palladium-catalyzed tandem Heck addition and ring opening reaction as well as for diboration reactions (Scheme a). Even more distant alkenyl biscyclopropyl carbinol 2 led to a completely diastereoselective Heck addition reaction before the subsequent selective double ring-opening.…”
mentioning
confidence: 99%